2019
DOI: 10.1097/meg.0000000000001307
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for predicting diabetes mellitus after the first attack of acute pancreatitis

Abstract: Background Diabetes mellitus can occur after acute pancreatitis (AP), but there are currently no tools for evaluating the risk of developing diabetes after an attack of AP. The aim of the study was to develop a nomogram for prediction of new-onset diabetes mellitus after the first attack of AP. Patients and methods We enrolled 616 patients with first-attack AP. We collected and statistically analyzed demographic data (age, BMI, and duration of hospitalization) and labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 41 publications
(54 reference statements)
2
29
2
Order By: Relevance
“…A certain role in the pathogenesis of diabetes in ACP is played by constitutionally determined tissue resistance, which is much more common in individuals with obesity and hyperlipidemia [14,15]. Obesity aggravates the clinical course of the disease and complicates its prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A certain role in the pathogenesis of diabetes in ACP is played by constitutionally determined tissue resistance, which is much more common in individuals with obesity and hyperlipidemia [14,15]. Obesity aggravates the clinical course of the disease and complicates its prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Such a big difference in the literature data on the incidence of DM with AP and CP is associated both with poor diagnosis of the underlying disease and with a different degree of probability of developing endocrine disorders in various forms of pancreatitis. It should be noted that carbohydrate tolerance is usually observed already in the early stages of observation [7,11,13,14]. DM can also form at the beginning of the clinical manifestation of pancreatitis, but still more often, the persistent disorder of carbohydrate metabolism occurs in about 5 years after the onset of the underlying disease, with chronic inflammation and on the background of frequent remissions of AP (2-3 times a year), when development of DM becomes a linear time dependence [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, each variable's weight is clear and expresses its relative importance (30). Although the logistic regression-based nomograms have long been used in diverse diseases (31,32,50,51), fewer attempts have been made to use nomograms in mental health studies. Our attempt represents a meaningful approach.…”
Section: Discussionmentioning
confidence: 99%
“…There has been limited exploration of other risk factors associated with increased endocrine dysfunction after AP. One study explored a predictive model for developing diabetes post-AP and created a nomogram [ 54 ]. The investigators found that body mass index, age, glucose, triglycerides and low-density lipoprotein at time of admission were associated with increased risk of DM over a 3-month follow-up period.…”
Section: Predictors Of Diabetes Of the Exocrine Pancreasmentioning
confidence: 99%
“…A c c e p t e d A r t i c l ediabetes post-AP and created a nomogram30 . The investigators found that body mass index (BMI), age, glucose, triglycerides and low-density lipoprotein(LDL) at time of admission were associated with increased risk of DM over a 3 month follow up period.This study highlights other comorbid conditions that may contribute to worsened impaired glucose metabolism after an AP episode.…”
mentioning
confidence: 99%